2024
DOI: 10.1186/s13287-024-03703-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cell-based optimization strategies for musculoskeletal regeneration: recent advances and perspectives

Chenrui Yuan,
Wei Song,
Xiping Jiang
et al.

Abstract: Musculoskeletal disorders are the leading causes of physical disabilities worldwide. The poor self-repair capacity of musculoskeletal tissues and the absence of effective therapies have driven the development of novel bioengineering-based therapeutic approaches. Adipose-derived stem cell (ADSC)-based therapies are being explored as new regenerative strategies for the repair and regeneration of bone, cartilage, and tendon owing to the accessibility, multipotency, and active paracrine activity of ADSCs. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 161 publications
(170 reference statements)
0
0
0
Order By: Relevance
“…Similar to tenocytes, uninduced ADSCs secrete collagen type I under general culture conditions [ 39 , 40 ]. Transmission electron microscopy studies have shown that the cells are rich in rough endoplasmic reticulum, indicating strong maintenance of secretion under co-culture conditions [ 41 ]. Therefore, ADSCs are an ideal source of seed cells for tendon tissue engineering due to their easy isolation, multiple differentiation potential and excellent responsiveness to microenvironmental stimuli [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to tenocytes, uninduced ADSCs secrete collagen type I under general culture conditions [ 39 , 40 ]. Transmission electron microscopy studies have shown that the cells are rich in rough endoplasmic reticulum, indicating strong maintenance of secretion under co-culture conditions [ 41 ]. Therefore, ADSCs are an ideal source of seed cells for tendon tissue engineering due to their easy isolation, multiple differentiation potential and excellent responsiveness to microenvironmental stimuli [ 42 ].…”
Section: Discussionmentioning
confidence: 99%